2002
DOI: 10.1264/jsme2.2002.98
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Growth of Acidocella facilis and Related Acidophilic Bacteria at High Concentrations of Aluminum.

Abstract: Acidophilic chemoorganotrophic bacteria of the genus Acidocella, Acidiphilium, and Acidobacterium were tolerant to concentrations of monomeric aluminum ion (Al 3+ ) of up to 100 mM in an acid medium of pH 3.5 or less. Furthermore, their growth was remarkably enhanced by the presence of aluminum. The maximum amount of Al absorbed was 2.02 mg·g dry cell wt -1 for Acidocella facilis. Aluminum phosphate as well as aluminum sulfate among aluminum chemicals tested provided for the most luxuriant growth of this bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Organisms related to G. ferruginea were not detected in the neutral/alkaline stream. Sequence analysis of DNA cloned from the acidic stream revealed that presumed acidophilic bacteria related to genera such as Acidocella, Acidiphilium, and Acidobacterium (8,31,32,37) were prevalent and comprised 7% of the total population of clones. Analysis of clones obtained from the very acidic stream revealed large representation by a few eukaryotic species (64% of clones), which were not deliberately targeted using the universal bacterial primers.…”
mentioning
confidence: 99%
“…Organisms related to G. ferruginea were not detected in the neutral/alkaline stream. Sequence analysis of DNA cloned from the acidic stream revealed that presumed acidophilic bacteria related to genera such as Acidocella, Acidiphilium, and Acidobacterium (8,31,32,37) were prevalent and comprised 7% of the total population of clones. Analysis of clones obtained from the very acidic stream revealed large representation by a few eukaryotic species (64% of clones), which were not deliberately targeted using the universal bacterial primers.…”
mentioning
confidence: 99%
“…Al + 3 ) become soluble in the soil as the pH drops below 5 and therefore may react with many chemical and cellular processes (Kochian 1995). As expected, many soil bacteria were reported to be tolerant to aluminium (Appanna et al 1994;Wakao et al 2002). For example, an acidophilic strain of Flavobacterium sp.…”
Section: Cerradomentioning
confidence: 73%
“…have been shown not only to be tolerant to aluminum, but also exhibited increased growth in its presence (Wakao et al, 2002). Aluminum phosphate and aluminum sulfate provided the greatest enhancement in growth at a pH of 3.5 and lower (Wakao et al, 2002). Acidocella sp.…”
Section: Aluminum Glazesmentioning
confidence: 99%